KOMODIFIKASI UPACARA NGABEN PADA MASYARAKAT HINDU DI DKI JAKARTA (Kajian Bentuk, Makna, dan Implikasi) - Untung Suhardi; Anak Agung Ketut Patera (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Based on the research I have done that this funeral procession is an implementation of the activities that have a religious ritual sacred functions and is linked between one another procession. The implementation in Jakarta ngaben different implementation cremation held in Bali that the implementation of cremation has been judged to be in accordance with the nature of thinking citizens jakarta high mobility, but in practice does not detract from the core implementation of the cremation. So that's besides the cremation ceremony for the dead to deliver atman abstract nature, it is also used to foster a sense of social solidarity with other Hindus. Implement holiness is essentially the purpose of human birth senagai, namely as a process of purification for all the sins of the past were not depleted of life enjoyed in the past is called karma Wasana so now's the life of man should strive to cleanse the sins of those. Agency is a tool to achieve dharma, artha, kama, moksanam, sariram, sadanam, therefore, through the agency of human trying to achieve a goal in life, that one way is by continuing to maintain the sanctity of her. Of implementation there is also the positive and negative aspects arising from the implementation of the implementation of the cremation.